Clinical challenges in mechanical ventilation. Issue 10030 (30th April 2016) - Goligher, Ewan C; Ferguson, Niall D; Brochard, Laurent J
Summary: Mechanical ventilation supports gas exchange and alleviates the work of breathing when the respiratory muscles are overwhelmed by an acute pulmonary or systemic insult. Although mechanical ventilation is not generally considered a treatment for acute respiratory failure per se, ventilator management warrants close attention because inappropriate ventilation can result in injury to the lungs or respiratory muscles and worsen morbidity and mortality. Key clinical challenges include averting intubation in patients with respiratory failure with non-invasive techniques for respiratory support; delivering lung-protective ventilation to prevent ventilator-induced lung injury; maintaining adequate gas exchange in severely hypoxaemic patients; avoiding the development of ventilator-induced diaphragm dysfunction; and diagnosing and treating the many pathophysiological mechanisms that impair liberation from mechanical ventilation. Personalisation of mechanical ventilation based on individual physiological characteristics and responses to therapy can further improve outcomes.